2018
DOI: 10.1002/jctb.5556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a sequential biotrickling–biofiltration unit for removal of VOCs from the headspace of crude oil storage tanks

Abstract: BACKGROUND Petrochemical refineries and production sites are considered to be the second greatest source of VOC emissions after vehicle exhausts. The feasibility and performance of a novel sequential biotrickling‐biofiltration unit for the treatment of a mixture of VOCs in the headspace of an oil and gas production tank battery was evaluated for three months at the Apache TAMU#2 well storage tank battery in Snook, Texas. RESULTS The results demonstrated that the main VOC constituents of the headspace of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In recent years, toluene has attracted increasing research attention [4][5][6]. Several techniques have been applied in controlling VOC emissions, including adsorption [7], absorption [8], photocatalysis [9], thermocatalysis [10], plasma catalytic oxidation [11], and biofiltration [12]. Among these methods, adsorption is an effective way to remove VOCs with low concentration and high velocity, because of its high efficiency and low cost [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, toluene has attracted increasing research attention [4][5][6]. Several techniques have been applied in controlling VOC emissions, including adsorption [7], absorption [8], photocatalysis [9], thermocatalysis [10], plasma catalytic oxidation [11], and biofiltration [12]. Among these methods, adsorption is an effective way to remove VOCs with low concentration and high velocity, because of its high efficiency and low cost [13].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the activity of the microorganisms in BTFs, the packing material is trickled continuously or intermittently by nutrient solution [47]. The most commonly used circulating liquid is a mineral salt solution [48]. Liquid flow through the packing material of a BTF provides humid conditions needed to support the biofilm growth and maintain the microbial activity [3].…”
Section: Biotrickling Filter Irrigation Systemsmentioning
confidence: 99%
“…The nutrient solution is supplied to the unit by a circulation pump. Khoramfar et al [48] studied VOC removal by BTF-BF unit and observed that due to continuous nutrient solution spraying, biofilm growth and consequently VOC removal was relatively higher in the BTF unit than in the BF unit [48]. Trickling liquid also washes out excess biofilm as well as degradation products that can hinder biodegradation of VOC [3].…”
Section: Biotrickling Filter Irrigation Systemsmentioning
confidence: 99%
“…These figures demonstrate the magnitude and scope of the problem. After vehicle exhaust emissions, the oil and gas processing industry's production facilities were identified as the second most significant source of VOC 10 . For example, the inventory of anthropogenic emissions in Russia shows that the oil and gas industries have a significant impact on the environment 11 .…”
Section: Introductionmentioning
confidence: 99%